Chronic Disorders of the Peroneal Tendons: Current Concepts Review of the Literature. Issue 16 (15th August 2019) - van Dijk, Pim A. D.; Kerkhoffs, Gino M. M. J.; Chiodo, Christopher; DiGiovanni, Christopher W.
Abstract : Chronic disorders of the peroneal tendons are a common cause of posterolateral ankle pain, including tendinopathy, tendon instability, and chronic tendon tears. They are often preceded by ligamentous instability or predisposing anatomic abnormalities such as a shallow fibular groove or a cavovarus foot deformity. Given the substantial disability associated with chronic peroneal tendon disorders, it is important for orthopaedic surgeons to optimize the diagnostic and treatment strategies of these entities based on contemporary studies. This article reviews both classic and recent scientific evidence regarding the diagnosis and treatment of patients with chronic peroneal tendon disorders.